Prevalence and Distribution of Rice Root Knot Nematode in Rice Nurseries in Chitwan and Lamjung Districts of Nepal - Tiwari, Srijan; Manandhar, Hira Kaji; Pandey, Prem; Nath, Shyam Sundar (Agronomy Journal of Nepal, 2024)
To determine the natural infection of the rice root-knot nematode (Meloidogyne graminicola Golden & Brichfield) in rice nurseries, a survey was carried out in Chitwan and Lamjung in June and July of 2022. Rice nurseries were randomly selected based on geographical location, agro-ecological region, land type, cropping practice, and soil type. Forty rice nurseries were surveyed i.e. twenty from each district and 100 seedlings from each nursery as the sample for the study using the simple random method of sampling were evaluated. Field survey revealed that M. graminicola was widely distributed in most rice growing areas of Chitwan and Lamjung districts. Most of the rice nurseries in Lamjung district were found to be infested with M. graminicola as compared to that of the Chitwan district. Disease severity was reported up to 23.26% in Lamjung and 20.2% in Chitwan district. Additionally, the study showed that dry bed conditions were more likely to be affected by rice root-knot disease than wet bed conditions. The majority of farmers planted seedlings on upland (dry) soil, where second-stage juvenile (J2) populations and rice root-knot disease were more common. Most farmers (87.5%) have limited knowledge about rice root knot nematodes and their control methods. This suggested a significant loss in rice output and a high danger of nematode multiplication. This information will provide knowledge about the prevalence of nematode and enabling rice growers in this region to design and implement an appropriate control strategy for managing M. graminicola.